Treatment of major depression disorder and bilateral angle-closure glaucoma comorbidity： a case report - Xing Mengjuan; Jin Zhixin; Sun Yang; Zhu Liping (Sichuan jingshen weisheng, 2021)
The purpose of this study is to describe the principles in selection and application of antidepressants in patients with depression complicating glaucoma or at high risk of glaucoma. With the aim of providing a partial reference for relevant issues， this paper elaborated a case of major depression after glaucoma surgery receiving 6 weeks of treatment with escitalopram oxalate and sulpiride achieved significant improvement in depressive and psychotic symptoms without triggering or exacerbating glaucoma.